2018
DOI: 10.1159/000490534
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biomarker in Diabetic Macular Edema with Serous Retinal Detachment: Serum Chitinase-3-Like Protein 1

Abstract: Purpose: To determine whether serum chitinase-3-like protein 1 (CHI3L1) and interleukin-6 (IL-6) levels correlate with serous retinal detachment (SRD) in diabetic macular edema (DME) using spectral-domain optical coherence tomography (SD-OCT). Methods: In this cross-sectional case-control study, 394 patients (treatment-naive DME patients, n = 218; diabetic patients without DME, n = 96; nondiabetic controls, n = 80) were included in the study. Eyes were classified according to SD-OCT features of DME: SRD, cystoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…In this study, patients with retinopathy (regardless of its progression) had significantly higher values of serum chitotriosidase, than those in whom retinopathy was still undetected. Our results support those observed in patients with type 2 DM and retinopathy, where the protein YKL-40, a member of the same family as chitotriosidase, had been proposed as a predictive marker of macular oedema and retinal detachment [7,25,28,29]. As in the case of neuropathy, serum levels of neopterin were increased in patients with retinopathy, but this variation lacked statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, patients with retinopathy (regardless of its progression) had significantly higher values of serum chitotriosidase, than those in whom retinopathy was still undetected. Our results support those observed in patients with type 2 DM and retinopathy, where the protein YKL-40, a member of the same family as chitotriosidase, had been proposed as a predictive marker of macular oedema and retinal detachment [7,25,28,29]. As in the case of neuropathy, serum levels of neopterin were increased in patients with retinopathy, but this variation lacked statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…For example, SRD is defined as fluid accumulation in the subretinal space as a result of retinal pigment epithelium dysfunction and damage to the external limiting membrane. 9,10 DRT results from ischemiainduced intracytoplasmic swelling of Müller cells, and if Müller cells have necrosis with cavity formation, CME results. 7,8 Several studies in the current literature aim to explain the effects of treatment modalities on SRD and non-SRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…DRT and CME are mainly caused by dysfunction of the inner blood-retinal barriers. [7][8][9][10] Due to differences in pathogenic mechanisms, DME can be divided in two groups: (1) SRD and (2) non-SRD (DRT CME).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of IL-6 in SRD type compared to DRT and CME also suggest that inflammation has an important role in pathogenesis. 20 The relationship between SRD and visual functions in diabetic macular edema is controversial. A post-hoc analysis of RISE and RIDE trials showed that the presence of baseline subretinal fluid was predictive for better visual outcomes than those without baseline SRD.…”
Section: Discussionmentioning
confidence: 99%